2005
DOI: 10.3168/jds.s0022-0302(05)73009-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Phenotypic Parameter Estimates of Total and Partial Lifetime Traits for Dairy Ewes

Abstract: A data file with 11,547 lactations for 2602 Spanish Churra ewes, daughters of 100 sires and 2179 dams, was used to estimate genetic and phenotypic parameters of total and partial lifetime traits with a multiple-trait animal model using REML. These ewes first lambed between 1992 and 1998 and belonged to 27 flocks enrolled in the nucleus scheme of the breed. The study took into account 4 life span traits, 2 productive traits, and 2 reproductive traits. Lifetime revenues from milk and lambs were calculated. Daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
3
10
1
1
Order By: Relevance
“…El-Saied et al (2005) (Brash et al, 1994) and 0.08 for Scottish Blackface (Conington et al, 2001)]. The heritability estimated for functional longevity in this study was higher than estimates reported by Chirinos et al (2007) in cattle, ranging between 0.05 and 0.07, whereas Neerhof et al (2000) and Ducrocq and Sölkner (1998b) reported heritabilities around 0.05 for the logarithmic scale and 0.22 for the real scale.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…El-Saied et al (2005) (Brash et al, 1994) and 0.08 for Scottish Blackface (Conington et al, 2001)]. The heritability estimated for functional longevity in this study was higher than estimates reported by Chirinos et al (2007) in cattle, ranging between 0.05 and 0.07, whereas Neerhof et al (2000) and Ducrocq and Sölkner (1998b) reported heritabilities around 0.05 for the logarithmic scale and 0.22 for the real scale.…”
Section: Discussioncontrasting
confidence: 51%
“…Longevity corrected for milk production level, functional longevity, is an approximate measure for involuntary culling (Dekkers, 1993). At present, only a few estimates of heritability for longevity are available in dairy sheep (Conington et al, 2001;El-Saied et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There are few reports in the literature of genetic parameters for ewe longevity in sheep, and those available generally suggest the trait is lowly heritable. For Churra ewes, estimates of the heritability for longevity ranged from 0.02 to 0.06 (El-Saied et al, 2005). Brash et al (1994) and Conington et al (2001) also reported low heritabilities for ewe longevity at 0.06 and 0.08, respectively, in Australian Dorset and Scottish Blackface sheep.…”
Section: Heritabilities Of Longevity Growth Body Composition Mouthmentioning
confidence: 99%
“…Different approaches are used for genetic evaluation of longevity including survival analysis (Ducrocq et al, 1988;Ducrocq, 1994) and linear models (Kersey DeNise et al, 1987;El-Saied et al, 2005). Survival analysis offers several advantages including use of censored and uncensored records (Vukasinovic et al, 1999;Caraviello et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As other lifetime traits in animal species, AFL has a skewed phenotypic distribution with evident over-representation of the right tail, thus discouraging its analysis under standard Gaussian-related mixed linear models (El-Saied et al, 2005). Both the generalization of Gaussian models to non-symmetrical patterns and the implementation of non-linear models on the basis of skew parametric distributions have been suggested in previous studies Casellas and Bach, 2012;García et al, 2014).…”
Section: Introductionmentioning
confidence: 99%